2019
DOI: 10.1590/s1980-65742019000010014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the external load of amateur soccer players during four consecutive training microcycles in relation to the external load during the official match

Abstract: The aim of this study was to assess the external load of amateur male players during 4 consecutive training microcycles (M) at the beginning of the in-season according to the training session in absolute external load demands and in relation to the competition demands. Methods: Regional-level players (n = 10; age, 20.8 ± 1.7 years; height, 175.5 ± 3.8 cm; body mass, 69.7 ± 2.9 kg; soccer experience, 13.2 ± 2.5 years) were monitored using GPS devices during training sessions and matches. The external load varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…The MD-1 was the lowest load in various studies whereas Owen et al [99] presented a higher ACC/DEC in MD-1 than MD-2. At amateur level, the MD+1 and MD-1 were less loading [91]. The observed main findings seemed to have been converging in a strategy tapering based on a gradual reduction until the last day before MD.…”
Section: Weekly Training Load and Match Load Distribution Analysismentioning
confidence: 81%
See 3 more Smart Citations
“…The MD-1 was the lowest load in various studies whereas Owen et al [99] presented a higher ACC/DEC in MD-1 than MD-2. At amateur level, the MD+1 and MD-1 were less loading [91]. The observed main findings seemed to have been converging in a strategy tapering based on a gradual reduction until the last day before MD.…”
Section: Weekly Training Load and Match Load Distribution Analysismentioning
confidence: 81%
“…Similarly, Owen et al [99] demonstrated that the MD-4 and MD-3 were the highest intensity and volume within the weekly microcycle, revealing a weekly highest load closer to MD. Anderson et al [87] and Sanchez-Sanchez et al [91] verified the greatest load in MD-3 and MD-2, respectively. The MD-1 was the lowest load in various studies whereas Owen et al [99] presented a higher ACC/DEC in MD-1 than MD-2.…”
Section: Weekly Training Load and Match Load Distribution Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Our main findings seem to be convergent in a strategy tapering based on a gradual reduction until the last day before MD. Normally, the training load pattern presents a progressive increase up to MD-3 and/or MD-4 followed by a decrease until MD-1 [21,[54][55][56]. In what concerns youth football, the literature reported an unloading prior to the pre-match training session [19,31,56].…”
Section: Inter-day Analysismentioning
confidence: 99%